Final Answer:
Substituting the expression of g(x) = x^2 + 2 into f(x) = 1/x - 5 gives us f(g(x)) = 1/(x^2 + 2) - 5. This simplifies to -5 - 1/(x^2 + 2).
Step-by-step explanation:
We are given two functions: f(x) = 1/x - 5 and g(x) = x^2 + 2.
We need to find f(g(x)), which means substituting the expression of g(x) into f(x) in place of x.
Substituting g(x) = x^2 + 2 into f(x) = 1/x - 5, we get: f(g(x)) = 1/(x^2 + 2) - 5
Combining terms, we simplify the expression to: f(g(x)) = -5 - 1/(x^2 + 2)
Therefore, the value of f(g(x)) is -5 - 1/(x^2 + 2), depending on the specific value of x used in the function g(x).